1997
DOI: 10.1007/s001250050808
|View full text |Cite
|
Sign up to set email alerts
|

Human leptin receptor gene in obese Japanese subjects: evidence against either obesity-causing mutations or association of sequence variants with obesity

Abstract: Leptin is an adipocyte-derived blood-borne satiety factor that acts on its cognate leptin receptor (Ob-R) in the hypothalamus, thereby regulating food intake and energy expenditure. To explore whether mutations in the Ob-R gene cause obesity in humans, we have searched for mutations in the gene for Ob-Rb, a biologically active receptor isoform, in obese Japanese subjects. We have also examined associations between such mutants and obesity in the Japanese. Genomic DNAs were used as templates in polymerase chain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
92
0
2

Year Published

1999
1999
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 141 publications
(107 citation statements)
references
References 36 publications
13
92
0
2
Order By: Relevance
“…Previous reports have suggested that allele frequency of the Arg223 of the Ob-R gene was higher in Japanese (0.838 ± 0.872) than in Caucasians (0.421 ± 0.440) and in Pima Indians (0.750). 29,30,33,51,52 These studies showed that allele frequency varies among ethnic groups and that the polymorphism is not associated with obesity. In this study, we observed an allele frequency similar to that reported by Matsuoka et al 30 Our data suggest that the Gln223Arg polymorphism of the Ob-R gene is not associated with obesity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous reports have suggested that allele frequency of the Arg223 of the Ob-R gene was higher in Japanese (0.838 ± 0.872) than in Caucasians (0.421 ± 0.440) and in Pima Indians (0.750). 29,30,33,51,52 These studies showed that allele frequency varies among ethnic groups and that the polymorphism is not associated with obesity. In this study, we observed an allele frequency similar to that reported by Matsuoka et al 30 Our data suggest that the Gln223Arg polymorphism of the Ob-R gene is not associated with obesity.…”
Section: Discussionmentioning
confidence: 99%
“…Several other polymorphisms have been found for the Ob-R gene. 30 Further studies are needed to determine association between the polymorphisms of the Ob-R gene and obesity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PCR primers to amplify the Gln223Arg variant analysed have been reported. 13 PCR ampli®cation was performed, with an initial denaturation (94 C, 5 min) then 94 C, 30 s, annealing at 60 C, 30 s, extension at 72 C, 30 s for 35 cycles followed by an additional extension (72 C, 5 min) with 1.5 mM MgCl 2 . PCR products were digested with MspI (Promega) to detect the Arg variant, which creates an MspI restriction site and analysed by gel electrophoresis (2.5% agarose gel).…”
Section: Methodsmentioning
confidence: 99%
“…34 No signi®cant differences in allele frequencies between non-obese (BMI 21.6AE 2.2 kgam 2 ) and obese (BMI 35.1 AE 6.5 kgam 2 ) Japanese subjects were observed for the K109R, Q223R, A976D and P1019P polymorphisms. 35 No differences in allele or genotype distributions of the 45 bp insertionadeletion polymorphism in the 3 H -UTS region of LEPR were observed between normal weight and morbidly obese (BMI ! 40 kgam 2 ) subjects.…”
Section: Introductionmentioning
confidence: 99%